ASSESSMENT OF THE CONTRIBUTION OF AGRICULTURAL EXTENSION SERVICE DELIVERY TO TOMATO FARMERS’ LIVELIHOOD IN KADUNA STATE, NIGERIA - Momodu, S.S.; Yusuf, O.H.; Musa, B.M. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
This study aimed to assess the contribution of Agricultural extension service delivery to tomato farmers’ livelihood in Kaduna State, Nigeria. A multi-stage sampling procedure was employed in selecting 214 tomato farmers. Data were collected using questionnaire and analyzed Z-test estimation analysis. The findings revealed that there was a significant increase (Z-value = 9.336) in the yield of tomato production at 1% level of probability due to agricultural extension services delivery. Based on the income and level of living of the tomato farmers, the results show that income (Z-value = 2.643) and level of living (Z-value = 2.880) were significant at 1% probability level. It is concluded that there was an improvement in yield, income, and level of living of tomato farmers as a result of utilizing extension service activities in the study areas. The study therefore recommends that to build on the success of participating farmers in tomato production, ensuring the long-term sustainability of agricultural extension services is crucial, thereby solidifying the gains made and supporting continued progress in the sector.